Integrating National Values in Educational Games: a Phenomenology Study at Methodist Kindergarten 5 Palembang - Jaya, Melinda Puspita Sari; Pamungkas, Joko (East Asian Journal of Multidisciplinary Research, 2024)
This paper aims to explain how the role and implementation of traditional games in instilling the character of love for the homeland in students of TK Methodist 5 Palembang. This type of research is qualitative-descriptive using a phenomenological approach. The methods used in this study are interviews, observation, and documentation. Triangulation techniques and the triangulation of sources determine the validity of the data in this study. Then, the data analysis technique uses the Milles and Huberman model to reduce, display, and verify data. The results of this study show that the habituation of traditional games can instill various kinds of national values that reflect the character of love for the homeland in students little by little. The national values formed through this game culture can be applied in everyday life and provide a way for students to live in society.